Insurance Company Liability for Denial of Cancer-Related Claims Against Policyholders - Raden Muhammad Ibnu Akbar; M. Khoirul Huda (The Easta Journal Law and Human Rights, 2026)
Humans experience various risks in their lives. An insurance company is an institution that can cover these risks. The form of risk transfer is an agreement with a reciprocal relationship, meaning that each party has rights and obligations that must be fulfilled. Sometimes the insured/policyholder has fulfilled their obligation to pay insurance premiums, but when a claim is made, the insurer, namely the insurance company, rejects the claim. This claim rejection occurs for various reasons, resulting in the policyholder suffering a loss. This insurance claim rejection usually occurs in life insurance that covers dangerous diseases such as cancer. This study will examine the responsibility of insurance companies for rejecting cancer claims against policyholders. Claim rejections must be based on legitimate, clear reasons, and in accordance with statutory provisions. Claim rejections that are carried out unilaterally, are not transparent, or contrary to the principle of good faith can be qualified as default or an unlawful act. This form of accountability can be in the form of an obligation to pay claims, provide compensation to policyholders and the possibility of imposing administrative sanctions by the Financial Services Authority if the insurance company is proven to have violated legal provisions in the insurance sector.